Effectiveness of government interventions on beneficiaries of land restitution : case of the Tshifhefhe Community of Makhado Municipality in Limpopo Province - Netshifhefhe, Justice Tshifhiwa (My University, 2021)
Globally, land reform has been a burning issue and where it was implemented, it has resulted in both successes and failures. The problems that engulf land reform illustrate that government’s programmes often fail to address the socio-economic conditions of the land claimants. As such, this study undertook to examine government interventions in addressing beneficiaries affected by land restitution in Limpopo province with specific reference to Tshifhefhe community located in Makhado Local Municipality. The study is an examination of governmental interventions in addressing beneficiaries affected by land restitution. The institutional mechanisms used to support land restitutions are considered for discussion. The study focused mainly at the Tshifhefhe community in Limpopo province where the need to restore the land forcibly taken from the community was considered. The restoration is necessary for improvement of their wellbeing, intensification of democracy and emancipation as well as restoration of previously marginalised people. The study adopted a qualitative approach and a case study design. The utilised approach described and explored Tshifhefhe beneficiaries’ perceptions, attitudes, views and feelings about the government’s interventions in their restored land. The findings point to the fact that government has been found to have provided inadequate support in terms of training on land management, marketing and administration of these beneficiaries including the Tshifhefhe restituted land. It is recommended that the government should intervene in the restored land projects by providing capacity building programmes, assessment of failures and successes in other restored land, mentoring, development and implementation of progressive and sustainable land policies and programmes.
Thesis (MPAM.) -- University of Limpopo, 2021
Keywords: Tshifhefhe community; Makhado Municipality; Government interventions; Beneficiaries; Land restitution; Land reform -- South Africa; Land reform beneficiaries